THE MEANING OF MARKETING STRATEGY THROUGH WORD OF MOUTH AND PACKAGING DESIGN ON CONSUMER PURCHASE DECISIONS: AN ETHNOGRAPHIC STUDY OF GTT YELLOW TOFU PRODUCTS IN KEDIRI CITY - Wiwik Setiyowati; Anita Sumelvia Dewi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to understand the meaning and mechanism of how word of mouth (WOM) communication and packaging design influence consumer perception and purchase decisions toward the local product GTT Yellow Tofu in Kediri City. Using a qualitative approach with mini-ethnography method, this research traces social and symbolic practices in culture-based traditional marketing. Data was collected through participatory observation, in-depth interviews with business owners and consumers, as well as visual documentation of packaging. Data analysis was conducted using the interactive technique of Miles, Huberman, and Saldaña (2014) through stages of open coding, axial coding, and selective coding to identify main themes. The research results show that WOM functions as a social mechanism that builds trust and community legitimacy, while packaging functions as a cultural symbol and marker of product authenticity. The interaction between both creates synergy between social trust and visual legitimacy that strengthens purchase decisions and consumer loyalty. Consumption of GTT Yellow Tofu is understood as a cultural practice that represents pride and local identity of Kediri society. Theoretically, this research expands understanding of culture-based marketing by integrating concepts of social capital and cultural branding, while practically providing guidance for MSMEs to develop marketing strategies that prioritize social values, cultural authenticity, and consumer trust.